2015
DOI: 10.1108/maj-12-2013-0973
|View full text |Cite
|
Sign up to set email alerts
|

Do audit opinions reflect earnings persistence?

Abstract: Purpose – The purpose of this paper is to examine the association between audit opinion and earnings persistence of listed companies in Thailand from 2004 to 2008. Design/methodology/approach – We use archival data and hand collected data in regression analysis. Content analysis was used to perform decomposition analysis of audit modifications. Findings – Firms receiving modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 54 publications
1
16
1
11
Order By: Relevance
“…Thus, audit opinion is negatively related to discretionary accruals in the case of the Romanian listed companies. Vichitsarawong and Pornupatham (2015) found that firms receiving modified opinions have lower earnings persistence than firms receiving unqualified opinions, and the degree of earnings persistence varies among types of modifications.…”
Section: Auditor Opinionmentioning
confidence: 99%
“…Thus, audit opinion is negatively related to discretionary accruals in the case of the Romanian listed companies. Vichitsarawong and Pornupatham (2015) found that firms receiving modified opinions have lower earnings persistence than firms receiving unqualified opinions, and the degree of earnings persistence varies among types of modifications.…”
Section: Auditor Opinionmentioning
confidence: 99%
“…Auditor akan mengeluarkan opini audit sebagai hasil dari proses audit yang telah dilakukan yang menunjukkan tingkat kewajaran laporan keuangan perusahaan (Tobing & Nirwana, 2004). Opini audit berperan penting bagi pengguna laporan keuangan, seperti investor, kreditor, dan para pemegang saham perusahaan karena dapat memberikan keyakinan bagi para pengguna laporan keuangan apakah informasi yang disajikan dalam laporan keuangan sudah sesuai dengan keadaan perusahaan yang sebenarnya dan standar akuntansi yang berlaku (Osesoga dan Ardianto, 2011).…”
Section: H1 Laba Tahun Lalu Berpengaruh Terhadap Laba Tahun Berjalanunclassified
“…Auditor akan memeriksa bukti atas informasi dalam laporan keuangan yang bertujuan untuk menentukan apakah laporan keuangan sudah tersaji sesuai dengan asersi yang telah ditentukan, yaitu keberadaan (occurence) atau keterjadian (existence), kelengkapan (completeness), hak dan kewajiban (rights and obligations), penilaian (valuation), penyajian dan pengungkapan (presentation and disclosure) (Arens, Elder, Beasley, & Hogan, 2012). Nantinya, auditor akan mengeluarkan opini atau pendapat atas kewajaran laporan keuangan sebagai hasil dari pemeriksaan yang telah dilakukan pada laporan keuangan perusahaan (Tobing & Nirwana, 2004 aspek yang bersifat material (Julianto, 2010).…”
unclassified
“…É esperada uma relação positiva com o retorno das ações, pois se espera que as empresas tenham sido auditadas por empresas com maior expertise (Pornupatham, 2015;Robu & Robu, 2015;Banimahd et al, 2013;Arruda et al, 2012); Risco = variável representativa de dependência financeira, sendo a relação entre passivo total e ativo total. Reflete a presença de capital de terceiros, de longo prazo, na estrutura de capital da firma, esperando-se uma relação negativa com o retorno (Pornupatham, 2015;Batista, Pereira, Silva & Imoniana, 2010); ROA = representativa de desempenho, sendo a relação entre o lucro operacional e a diferença entre ativo total e lucro líquido. Espera-se que o maior desempenho impacte positivamente no retorno das ações (Robu & Robu, 2015;Ianniello & Galloppo, 2012); Tam = logaritmo do ativo total.…”
Section: Metodologiaunclassified
“…Espera-se que o maior desempenho impacte positivamente no retorno das ações (Robu & Robu, 2015;Ianniello & Galloppo, 2012); Tam = logaritmo do ativo total. É esperado que empresas maiores apresentem maiores retorno das ações (Pornupatham, 2015;Czernkowski et al, 2010); Mg = margem líquida, calculada pela relação entre lucro líquido e receitas de vendas. O resultado esperado com o retorno é positivo (Robu & Robu, 2015); Liqseca = liquidez seca, calculada pela relação entre a diferença de ativo circulante e itens não caixa com o passivo circulante.…”
Section: Metodologiaunclassified